Nutrition Literacy of Middle School Students and Its Influencing Factors: A Cross-Sectional Study in Chongqing, China - Mao Zeng; Mao Zeng; Mao Zeng; Mao Zeng; Yuzhao Zhu; Yuzhao Zhu; Yuzhao Zhu; Zhengjie Cai; Zhengjie Cai; Zhengjie Cai; Zhengjie Cai; Jinli Xian; et al. (Frontiers Media S.A., 2022)
Nutrition literacy plays an important role in children's dietary habits and nutrition. This study aimed to analyse the status of nutrition literacy and its influencing factors amongst middle school students in Chongqing, China. "Nutrition literacy scale for middle school students in Chongqing" was used in 29 districts of Chongqing in September 2020. The scores of nutrition literacy and its' three sub-domains (functional, interactive and critical nutrition literacy) were divided into low and high groups based on their median scores. Binary logistic regression was used to measure the influencing factors of nutrition literacy. A total of 18,660 middle school students were included in this study. The median of nutrition literacy of middle school students was 61.68 (IQR = 14.37). Interactive nutrition literacy had the highest score (median = 70.00, IQR = 20.00), followed by functional nutrition literacy (median = 68.69, IQR = 14.14) and critical nutrition literacy (median = 45.83, IQR = 25.00). Students who were the minority (OR = 0.71, 95% CI = 0.637-0.785), in senior high school (OR = 0.51, 95% CI = 0.477-0.548), in rural areas (OR = 0.85, 95% CI = 0.790-0.911), receiving school meal support from the government (OR = 0.63, 95% CI = 0.591-0.664), with other caregivers' parenting (OR = 0.86, 95% CI = 0.805-0.914), with parents having a low level of education and with an abnormal BMI [thin (OR = 0.91, 95% CI = 0.837-0.990), overweight (OR = 0.87, 95% CI = 0.785-0.968), and obese (OR = 0.83, 95% CI = 0.767-0.902)] presented less probability of being a high level of nutrition literacy. Our results could assist public health authorities in developing strategies of nutrition literacy promotion for references and theoretical foundations.